A Review of the Role of Milk and Dairy Products in the Development of Obesity and Cardiometabolic Disease. (29th May 2020) - Dougkas, Anestis; Hobbs, Ditte
Abstract: Objectives: The consumption of milk and dairy products makes an important contribution to children's nutrient intake, yet due to relatively high saturated fat content, the health benefits of dairy products have come under question and public health advice is often perceived as unclear. This review aimed to provide an overview of the current available evidence taken from systematic reviews and meta-analyses on dairy product consumption and risk of obesity, type 2 diabetes (T2D) and cardiovascular disease (CVD) in children, adolescents, and adults. Methods: The literature of English-language systematic reviews and meta-analyses published up to September 2019 was reviewed by searching the following three databases: ISI Web of Science, PubMed, and Google Scholar. Search terms included 'dairy', 'milk', ' yogurt', 'obesity', 'adiposity', 'bodyweight', 'type 2 diabetes', 'cardiovascular diseases', 'coronary heart disease', 'blood pressure', 'insulin resistance', 'glucose', 'children', 'adolescents', 'adults' and combinations of these. Published work on calcium supplementation was excluded. Results: Milk and certain dairy products were found to be not associated with or inversely associated with obesity in children and adolescents. In adults, consumption of milk and dairy products improves body composition and enhances weight loss during energy restriction diets, while it has a neutral effect on body weight in maintenance diets. Prospective cohort studies suggest that the consumption of dairy products, with regular or low-fat content, does not adversely affect the risk of T2D or CVD outcomes and may have a protective effect. The plausible mechanisms underlying the effect of dairy nutrients on obesity and cardiometabolic disease are incompletely understood but may include effects on lipolysis, lipogenesis and fatty acid absorption. Conclusions: Dairy product consumption, as part of a balanced diet, may protect against the risk of obesity, T2D, and CVD. However, further research is needed to better understand the role of different types of dairy products and of different fat content in obesity, T2D, and CVD. The new and emerging range of products (including plant-based alternatives) being used as dairy milk substitutes has yet to be evaluated in scientific studies. Funding Sources: None.